The Relationship Between Narcissistic Behavioral Tendencies and Facebook Addiction in Students - Josefin Gemilani Nalenan; Dian Lestari Anakaka; Rizky Pradita Manafe (Journal of Health and Behavioral Science, 2022)
Facebook is one of the most popular social media among the public. Facebook is one of the online social networking or social networking sites created to provide technological facilities with the intention that users can socialize or interact in cyberspace. Someone addicted to making Facebook an important cause that can't be given up. The hypothesis in this study is that there is a significant association between narcissistic behavior and Facebook addiction among students at State Vocational High School 2 Kupang City. The participants in this study were students from Kupang City State Vocational High School 2, a total of 226 respondents. This study uses correlation analysis. The result of the analysis shows that there is a correlation coefficient between the variable’s narcissistic behavior and Facebook addiction of 0.771 with a significant value of 0.000 < 0.05.